Insights into the Mechanisms Underlying Boron Homeostasis in Plants - Yoshinari, Akira; Takano, Junpei (Frontiers in Plant Science, 2017)
Boron is an essential element for plants but is toxic in excess. Therefore, plants must adapt to both limiting and excess boron conditions for normal growth. Boron transport in plants is primarily based on three transport mechanisms across the plasma membrane: passive diffusion of boric acid, facilitated diffusion of boric acid via channels, and export of borate anion via transporters. Under boron -limiting conditions, boric acid channels and borate exporters function in the uptake and translocation of boron to support growth of various plant species. In Arabidopsis thaliana, NIP5;1 and BOR1 are located in the plasma membrane and polarized toward soil and stele, respectively, in various root cells, for efficient transport of boron from the soil to the stele. Importantly, sufficient levels of boron induce downregulation of NIP5;1 and BOR1 through mRNA degradation and proteolysis through endocytosis, respectively. In addition, borate exporters, such as Arabidopsis BOR4 and barley Bot1, function in boron exclusion from tissues and cells under conditions of excess boron. Thus, plants actively regulate intracellular localization and abundance of transport proteins to maintain boron homeostasis. In this review, the physiological roles and regulatory mechanisms of intracellular localization and abundance of boron transport proteins are discussed.